Metode Konvolusi Dalam Menghitung Peluang Kebangkrutan Suatu Perusahaan Asuransi - Yuli Andriani (Faculty of Mathtmatics and Natural Sciences, 2008)
Calculating ruin probability is required by Insurer in designing portofolio for knowing risk values in portofolio. Convolution method in calculating ruin probability focused in surplus process that is Un. Un only depands on Un-1 state. Then convolution method is expanded by evaluating ruin probability of finite time discrete horizon. While it was capability using this method, all random variables of distribution must be used discrate.